Quality Markers for Astragali Radix and Its Products Based on Process Analysis - Dai, Yuntao; Wang, Dongbo; Zhao, Manjia; Yan, Lihua; Zhu, Chao; Li, Pengyue; Qin, Xuemei; Verpoorte, Rob; Chen, Shilin (Frontiers in Pharmacology, 2020)
Due to the complex nature of traditional medicines, quality control methods need to cover two aspects: compliance of raw materials with quality standards and process control. Astragali radix (AR), the roots of Astragalus membranaceus, was selected in this study as an example of a widely used traditional medicine in various formulations. Astragaloside IV (AG IV) and calycosin 7-O-β-D-glucoside (CG) are used as the markers for the quality control of AR and its products in the Chinese Pharmacopoeia. However, in the raw materials, malic acid esters of the CG and acetate esters of the astragaloside are easily decomposed into CG and AG IV during storage and processing of AR to make extracts for various formulations. The thermal stability of the isoflavonoids and astragalosides in decoction was studied. The level of CG and astragalosides (AG I/ AG II/ AG IV) was strongly affected by prolonged heat during processing, while calycosin was stable in the conditions. Also the major astragalosides in AR could fully converted into AG IV which eventually reaches a stable level under certain conditions. With calycosin and AG IV as marker components, practical, reproducible, and precise methods were established and applied to the quality analysis of AR from its raw materials to its intermediates and products. This study demonstrates that a full chemical profiles analysis of the whole manufacturing process (from “raw materials—intermediates/extracts—final product”) is important to identify quality markers (Q-markers) and even to establish proper analysis methods for traditional Chinese medicine products.